Feasibility study by simulation of a small sized Stirling engine for cooling generation. - Auñón-Hidalgo, Juan Antonio; Nuñez-Gevorkian, Daniel (My University, 2023)
Over the years, the demand for energy is increasing worldwide mainly due to population and consumption growth. At this point, Stirling engines play a very important role due to their high efficiency and reliability and their simple and compact mechanism. The Stirling engine bases its operation on the Stirling cycle if the objective is to obtain energy from the heat transfer between the hot focus and the cold focus [1] [2]. In the same way, stirling cycles can be used in reverse mode. In this type of machines, the mechanical energy produced by an electric generator is used to extract heat from the cold focus and reduce its temperature, the applications of these cycles can range from a few degrees (maintenance of beverages, etc...) to cryogenic temperatures. The objective of this work is to analyze the operation of a low temperature Stirling of the company PHYWE, transparent model 04372-00. A CFD simulation has been developed using ANSYS software and the model has been validated by means of laboratory tests and results of experimental tests carried out by the manufacturer.
Keywords: Motores térmicos; Refrigeración y máquinas frigoríficas; Stirling engine; Cooling generation; Simulation